A new dwarf species of Proceratophrys Miranda-Ribeiro, 1920 (Anura, Cycloramphidae) from the highlands of Chapada Diamantina, Bahia, Brazil - Junior, Mauro Teixeira; Amaro, Renata Cecília; Recoder, Renato Sousa; Dal Vechio, Francisco; Rodrigues, Miguel Trefaut (Zootaxa, 2012)
A new species of Proceratophrys is described from the highlands of northeastern Brazil. Molecular and morphologicaldata suggests that Proceratophrys redacta sp. nov. is sister to P. minuta, and related to P. schirchi and P. cristiceps. Thenew species is diagnosed by its small size, absence of rostral and palpebral appendages, sagittal ridges interrupted, absenceof postocular swellings, snout vertical in profile and dorsal coloration lacking distinct ocelli. The new species representsanother example of endemism for the genus Proceratophrys in Chapada Diamantina region, and of another appendagelesssmall-sized species associated with highlands. The phylogenetic results indicate that current morphological groupings in Proceratophrys may not represent natural groups.